Gender, Entry Regulations, and Small Firm Informality : What Do the Micro Data Tell Us? - McKenzie, David (World Bank, Washington, DC, 2012)
Informality is pervasive in many developing countries, where the majority of businesses do not register. One view, linked strongly with Hernando de Soto and the International Finance Corporations (IFC's) doing business project, is that the informal sector consists of potential entrepreneurs who remain small as the administrative and financial costs of becoming formal prevent firms from formalizing, but that formalization is needed to obtain access to finance, and have the incentive to grow without fear of government inspectors. Moreover, it is often argued further that the burden of regulation is even larger for female business owners, because they have less time and money to overcome expensive and time-consuming barriers to registration. As a result, doing business 2008 claims that the benefits of business regulation reform are especially high for women, and shows that across countries there is a positive association between the percentage of entrepreneurs who are women and the ease of doing business. This note largely focuses on the implications for micro and very small enterprises in urban areas, which comprise most businesses in developing countries. Almost all rural firms are informal.